Biculturalism and Personnel Administration - Malo, Fernand-G. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1968)
The author explains the historical reasons for the distribution of Canadians in industry along cultural-linguistic lines, describes the present evolution toward a better equilibrium, the problems thus posed and the prerequisites — both individual and institutional — for their proper solution on the basis of increased efficiency through respect for cultural differences and rational use of people of both languages.